2014
DOI: 10.1186/1471-2407-14-39
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pain severity on the quality of life in patients with head and neck cancer before antineoplastic therapy

Abstract: BackgroundThe aim of this study was to assess the severity of pain and its impact on the quality of life (QoL) in untreated patients with head and neck squamous cell carcinoma (HNSCC).MethodsA study group of 127 patients with HNSCC were interviewed before antineoplastic treatment. The severity of pain was measured using the Brief Pain Inventory (BPI) questionnaire, and the QoL was assessed with the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core-30 (EORTC QLQ-C30) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 36 publications
7
44
2
3
Order By: Relevance
“…A cross‐sectional study on patients with advanced prostate cancer (Charalambous & Kouta, ) found that cancer‐related fatigue affects HRQoL in various ways, such as increased dependency on others, loss of power over decision‐making and daily living disruption. Another study on people with head and neck cancer (Oliveira et al, ) found that the severity of pain is statistically related to advanced stages of cancer and that it directly affects HRQoL. These results indicate that compensation for or reduction in the level of fatigue and pain might be of importance when aiming to enhance HRQoL of people with advanced cancer.…”
Section: Discussionmentioning
confidence: 96%
“…A cross‐sectional study on patients with advanced prostate cancer (Charalambous & Kouta, ) found that cancer‐related fatigue affects HRQoL in various ways, such as increased dependency on others, loss of power over decision‐making and daily living disruption. Another study on people with head and neck cancer (Oliveira et al, ) found that the severity of pain is statistically related to advanced stages of cancer and that it directly affects HRQoL. These results indicate that compensation for or reduction in the level of fatigue and pain might be of importance when aiming to enhance HRQoL of people with advanced cancer.…”
Section: Discussionmentioning
confidence: 96%
“…On the contrary, others (Law et al 2015) used a cut-off of seven or more in a NRS to define severe pain as the main outcome. This study considered four or more in the NRS as a reasonable clinical parameter for pain, as moderate or severe pain seems to influence quality of life more than mild Pain of endodontic origin Gomes et al or no pain (Oliveira et al 2014b). Additionally, visual analogue scales (VAS) and numeric rating scales (NRS) for assessment of pain intensity agree well, are equally sensitive in assessing acute pain, and are superior to a four-point verbal categorical rating scale (Breivik et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…chemotherapy (CT)-induced mucositis, surgical removal of tumours, musculoskeletal symptoms from hormone therapy, HT] (Grond et al 1996;Davis & Parala-Metz 2013). Cancer-related pain substantially impairs the quality of life of patients (Kroenke et al 2010;Oliveira et al 2014).…”
Section: Introductionmentioning
confidence: 99%